Road condition reporting: crowd sourcing on android smart phone - Wan Adnan, Wan Azizun; Yap, W. H.; Hashim, Shaiful Jahari; Syed Ahmad, Sharifah Mumtazah; Hanafi, Marsyita (2013)
Hazardous road conditions such as potholes are usually reported by public either by phone or filling a form in the appropriate authorities website for the necessary actions to be taken. This required a longer time to solve the problem as the information provided may not be sufficient for action to be taken such as location and the picturing of the real situation might not be available. By implementing crowd sourcing concept in the smart phone application, it can provide a great combination as a tool to collect data from public. This paper proposed a mobile application that allows the public to easily report damages and potholes on roads to the appropriate authorities. This developed application has shortened the duration of relevant information received since user can immediately send to the authority's server through their mobile phone.